Medieval Renaissance Baroque: A Cat's Cradle in Honor of Marilyn Aronberg Lavin - Levine, David A.; Freiberg, Jack (Italica Press, Inc., 2010)
"Medieval renaissance Baroque" celebrates Marilyn Aronberg Lavin's breakthrough achievements in both the print and digital realms of art and cultural history. Fifteen friends and colleagues present tributes and essays that reflect every facet of this renowned scholar's brilliant career. Tribute presenters include Ellen Burstyn, Langdon Hammer, Phyllis Lambert, and James Marrow. Contributors include Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, and Gary Schwartz. 79 illustrations, bibliography of Marilyn Lavin's works, index.
Keywords: dept.art